Malaysian finance sector weak-form efficiency: Heterogeneity, structural breaks, and cross-sectional dependence - Ching Kok, Sook (2015)
This study examines the weak-formefficientmarkethypothesis (EMH)for the Finance Sector inMalaysian Stock Exchange, by exploring and scrutinizing the firm-level efficiency over for the period from 1 st January 1997 to 31st December 2014. For this purpose, we apply panel nonlinear unit root test that accounts for heterogeneity, and panel stationarity test to allow for the presence of structural breaks and crosssectional dependence (CSD). The main findings of this study suggest the following: first, there is a strong CSD among the price series of finance stocks; second, unlike the traditional panel unit root tests that provide mixed-results, the panel stationarity test which incorporates structural breaks and CSD suggests that these series are characterized as random walk processes implying the Finance Sector is weak-form efficient. The finding of weak-form efficiency has salient implications in terms of capital allocation, stock price predictability, forecasting technique, and the impact of shocks to stock prices. Doi: http://dx.doi.org/10.1016/j.jefas.2015.10.002